Efficacy of Group Schema Therapy on Difficulty in Emotion Regulation and Aggression in Adolescent Girls - Mozhgan Yazdani (Alzahra University, 2021)
The purpose of this study was the effectiveness of schema therapy on the difficulty in emotion regulation and aggression in adolescent girl students. The research method was Quasi-experimental with pre-test, post-test, and two-month follow-up with the control group. The statistical population of this study included all-female high school students in the year 2019-2020, that using the purposive sampling method, 40 of them were selected and randomly assigned to the experimental and the control group (each group of 20 people). Emotion Difficulty Regulation Questionnaire and Aggression Questionnaire were used in three steps to collecting data. The experimental group received Schema Therapy (8 sessions 90 minutes) but the control group received no treatments. Data were analyzed using repeated-measures ANOVA. The results showed that schema therapy was effective in reducing all subscales of difficulty in regulating emotion and aggression in adolescent female students. But over time, this effect was significantly reduced in the follow-up phase. In fact, schema therapy, by working on the multidimensional dimensions of the individual, provides the ground for change and is effective. Adolescence itself is associated with difficulty in cognitive regulation and behavioral abnormalities, including aggression, so schema therapy can be used as a means of reducing the difficulty in cognitive regulation and aggression in the adolescent.